New mammalian transforming retrovirus: demonstration of a polyprotein gene product. - Rapp, U R (1983)
A new acute transforming type C retrovirus was isolated from mice inoculated with a virus stock obtained by iododeoxyuridine induction of methylcholanthrene-transformed C3H/10T1/2 mouse cells. This virus, designated 3611-MSV, transforms embryo fibroblasts and epithelial cells in culture and induces fibrosarcomas in vivo. 3611-MSV is replication defective, requiring a type C helper virus for propagation both in vitro and in vivo. By using endpoint transmission of 3611-MSV to MMCE C17 mouse and FRE 3A rat cells, several nonproductively transformed clonal cell lines have been derived. Pseudotype virus stocks obtained from such clones transform cells in vitro, are highly oncogenic in vivo, and exhibit host range and serological properties that are characteristic of their helper virus component. Analysis of viral antigen expression in 3611-MSV-transformed cells has led to the demonstration of a 90,000-molecular-weight (Mr) polyprotein and a 75,000-Mr probable cleavage product, both containing the amino-terminal murine leukemia virus gag gene proteins p15 and p12. In contrast to gene products of many previously described mammalian transforming viruses, 3611-MSV-encoded polyproteins lack detectable protein kinase activity, and 3611-MSV-transformed cells resemble chemically transformed cell line C3H/MCA-5, from which 3611-MuLV was originally derived, in that they do not exhibit elevated levels of phosphotyrosine. By using molecular hybridization the 3611-MSV transforming gene was found to be distinct from previously described mammalian cellular oncogenic sequences, including c-ras, c-abl, c-fes, c-fms, c-sis, and c-mos.